Hepatitis B markers in heterosexual patients attending two genitourinary medicine clinics in the West Midlands. Issue 2 (April 1997) - el-Dalil, A A; Jayaweera, D T; Walzman, M; Radcliffe, K W; Richmond, R; Wade, A A; Shahmanesh, M
Abstract : OBJECTIVE: To determine the prevalence of hepatitis B virus (HBV) infection in heterosexual patients attending two genitourinary medicine (GUM) clinics in the West Midlands and to examine whether heterosexual activity is a risk factor for acquiring HBV infection with the view to extend HBV vaccination policies to cover this group. DESIGN: HBV markers were determined in the GUM study group and compared with that of the control groups. Responses to a questionnaire were used to examine sexual behaviour patterns that may be related to heterosexual acquisition of HBV infection. SETTING: The West Midlands, UK April 1992-January 1993. SUBJECTS: 788 male patients and 688 female patients attending GUM clinics were compared with 498 male blood donors and 563 females attending antenatal clinics for the seroprevalence of HBV markers. Potential risk factors related to heterosexual activity were assessed in 1436 patients in the study group. MAIN OUTCOME MEASURES: Prevalence of HBV markers in the GUM study group and the controls. The possible use of the risk factors examined as predictors for acquiring HBV infection. RESULTS: The seroprevalence of hepatitis B core antibody (anti-HBc) in GUM patients was 1.9% and 0.5% in the control group. In the study groups the prevalence of anti-HBc from Birmingham was 3.2% while that from Coventry was 0.8%. The low seroprevalence of HBV prevented a multiple logistic analysis. A limited regression analysis showed that being non-white (p < 0.001) and duration of sexual activity (p = 0.013) were risk factors for HBV infection. However, these two factors were poor predictors of the risk to exposure to HBV infection. CONCLUSION: The prevalence of HBV infection in heterosexual patients in the West Midlands is very low and does not provide any indications to broaden HBV vaccination into heterosexual patients attending GUM clinics. Risk factors were poor predictors of the exposure to HBV infection. This is partially due to the low prevalence of HBV infection in this study. Further studies are required before definitive conclusions are made regarding the potential predictive value of risk factors.